Rationalization of Rainfall Station Network in Welang Watershed Using Kagan-Rodda Method - Safira Anisah Haromain; Sri Wahyuni; Lily Montarcih Limantara (U Karst, 2022)
Rationalizing rainfall station is important to get an effective and efficient number and distribution of rainfall stations. If rationalization isn’t carried out, it affect to operating and maintenance costs of rainfall stations and accuracy of data. This study aimed to evaluate existing rainfall station and rationalize rainfall station, so rainfall station’s location is evenly distributed. This study is located in Welang watershed with an area 477.78 km2. This research requires rainfall ground data from 9 rainfall stations and CHIRPS satellite rainfall data from Google Earth Engine. The data is tested with consistency, stationary, suitability, and rationalization based on World Meteorological Organization (WMO) standards and Kagan-Rodda method. Later, new rainfall station networks will be obtained with the influence area of rainfall stations suitable to WMO Standard. CHIRPS data is highly suitable with ground data, proven by high NSE, strong correlation, and low relative error, so CHIRPS data can be used for further analysis. According WMO, only 1 rainfall station in Welang watershed has been suitable for WMO standard. Those unsuitable with WMO standards need to be rationalized. Based rationalization results, with average error <10%, Welang watershed requires 4 rainfall stations by maintaining Lawang Station, moving Telebuk to Station B, Selowongko to Station C, and Tutur to Station D. The influence area of recommendation rainfall stations have been suitable to WMO Standards and obtained even distribution rainfall stations. This recommendation are expected to be considered by relevant institutes to move the location of the rainfall station to get more accurate rainfall data.